Removal of Nitrate onto Spent Tea Leaves and Spent Coffee Grounds in a Fixed Bed Column - Noor Adlin Afriena Che Abd Halim (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To investigate and compare the percentage of removal efficiency of nitrate in water by using ing spent tea leaves and spent ground coffee as adsorbent. To evaluate process parameter for the nitrate removal using the best adsorbent for continuous operation in fixed bed column. To predict the breakthrough time of the process and mass transfer behaviour in the process.